Topographical organization of projections to cat motor cortex from nucleus interpositus anterior and forelimb skin - Jörntell, Henrik (Blackwell Science Inc, 1999)
1. The activation of the motor cortex from focal electrical stimulation of sites in the forelimb area of cerebellar nucleus interpositus anterior (NIA) was investigated in barbiturate-anaesthetized cats. Using a microelectrode, nuclear sites were identified by the cutaneous climbing fibre receptive fields of their afferent Purkinje cells. These cutaneous receptive fields can be identified by positive field potentials reflecting inhibition from Purkinje cells activated on natural stimulation of the skin. Thereafter, the sites were microstimulated and the evoked responses were systematically recorded over the cortical surface with a ball-tipped electrode. The topographical organization in the motor cortex of responses evoked by electrical stimulation of the forelimb skin was also analysed. 2. Generally, sites in the forelimb area of NIA projected to the lateral part of the anterior sigmoid gyrus (ASG). Sites in the hindlimb area of NIA also projected to lateral ASG and in addition to a more medial region. Sites in the face area of NIA, however, projected mainly to the middle part of the posterior sigmoid gyrus (PSG). 3. For sites in the forelimb area of NIA, the topographical organization and strength of the projections varied specifically with the cutaneous climbing fibre receptive field of the site. The largest cortical responses were evoked from sites with receptive fields on the distal or ventral skin of the forelimb. 4. Microelectrode recordings in the depth of the motor cortex revealed that responses evoked by cerebellar nuclear stimulation were due to an excitatory process in layer III. 5. Short latency surface responses evoked from the forelimb skin were found in the caudolateral part of the motor cortex. At gradually longer latencies, responses appeared in sequentially more rostromedial parts of the motor cortex. Since the responses displayed several temporal peaks that appeared in specific cortical regions for different areas of the forelimb skin, several somatotopic maps were seen. 6. The cerebellar and cutaneous projections activated mainly different cortical regions and had topographical organizations that apparently were constant between animals. Their patterns of activation may constitute a frame of reference for investigations of the functional organization of the motor cortex.